Mindfulness as Moderator Against Emotional Exhaustion Due to Online Teaching During COVID-19 Pandemic: An Investigation Using Job Demands-Resources Model and Conservation of Resource Theory - Hsieh, Chuan-Chung; Ho, Sophia Shi-Huei; Li, Hui-Chieh; Liang, Jyun-Kai (Frontiers in Psychology, 2021)
On the basis of the Conservation of Resource (COR) theory and using the Job Demands-Resources (JD-R) model, this study examines the relationships among job demands and job resources of online teaching (JD-OT and JR-OT), perceived instructional efficacy of OT (PIE-OT), mindfulness in teaching (MiT) and emotional exhaustion (EE) to understand the psychological stress experienced by teachers engaged in OT and how mindfulness has moderating effects on relieving anxiety and preventing burnout. A total of 476 teachers with OT experience completed online a self-report survey with items adapted from related scales. The hypotheses were validated using structural equation modeling. Causal relationships were assessed using path analysis and multi-group analysis was performed to examine the moderating effect of MiT. JD-OT has significant and negative impact on PIE-OT, JR-OT has significant and positive impact on PIE-OT, and PIE-OT has significant and negative impact on EE. Moreover, PIE-OT mediates the positive relationship of JD-OT with EE and the negative relationship of JR-OT with EE. The moderating role of MiT in the relationship of JD-OT and JR-OT with PIE-OT was also validated. In OT work environments, teachers have great need and desire for JR, which can have a positive impact on PIE. Mindfulness training contributes to improving OT efficacy and reducing EE. Enhancing teachers’ MiT enables them to deal with demands from work and their superiors and motivates them to respond with ease to the stressful external environment.